Análisis del periodismo en contextos de violencia, causas y vías de solución desde la perspectiva de los medios afectados entre 2021 - 2023 - Paredes Miranda, Tannia Rosa (2024)
Security is of vital importance in Journalism because in this way the desire to elucidate the truth in the society that surrounds the communicator is greatly deepened through his daily work, if this were to perish soon, that is how quickly would be lost the job of a social actor, who ensures that the axes of power fulfill their obligations correctly. In a country like Ecuador where the laws that are associated with the communicator are merely placed for a deontological value, therefore, they do not support their integrity, but rather force them to work daily in risk scenarios without jurisprudential support that ironically added to the corruption of those who should safeguard his life, they leave him adrift, making difficult the task of reporting with comfort. Hence, through interviews with journalists and relatives of victims who worked as communicators, the passion is associated that sometimes makes them forget that they are also human, and that with a deadline in this world, taking care of their lives over their careers is the most reasonable, falling on the conclusive response of a psychologist who professionally assesses how bearable the diffusive duty and its collateral aspects are. A historical and legal compendium is also collected to exemplify what the results have been from the actions taken by various researchers in different risk scenarios, while some unfortunately ignored the safeguard of their existence, others valued a little more this that allows them to disclose new data in the future; the legal framework is equally necessary to rescue since after an exhaustive analysis of the regulations of the Republic of Ecuador, such as the Constitution, the Organic Law of Communication and Presidential Decree 850 of the Lasso Government, attached to Human Rights, it is described that together they are a worth of legal protection for other professionals; That is why the opinion of the citizens or audience is also titrated for its importance in directing the reins of the country indirectly through the Assembly in a democratic way, it is a call to action so that the situation of insecurity in Ecuador changes to favor of the masses, and of the communicators themselves who also make them up.